Enhancing Quality in Transnational Higher Education: Experiences of Teaching and Learning in Australian Offshore Programs - Chapman, A.; Pyvis, David (Lexington Books, 2012)
Enhancing Quality in Transnational Higher Education explores issues and questions concerning the provision of quality teaching and learning in university programs delivered 'offshore'. The focus of the book is on what makes for a good and successful education in the context of transnational programs of Australian universities. The book traces research by the authors into the 'lived experiences' of teachers and learners engaged in Australian transnational education across a broad range of universities, locations, programs and models of delivery. The enormous trend towards the delivery of university programs across national borders is compelling evidence of the internationalization of higher education in the 21st century. Universities worldwide are challenged to provide quality assurance for this new kind of education. For universities, this book offers principles to enhance existing frameworks for assuring the quality of learning and teaching in university offshore education programs. The book will also be of particular interest to academics of higher education institutions who are involved in the policy and practice of transnational education.